2022
DOI: 10.1037/pne0000262
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing in autism across exteroceptive and interoceptive domains.

Abstract: Objective: The current article discusses recent literature on perceptual processing in autism and aims to provide a critical review of existing theories of autistic perception and suggestions for future work. Method: We review findings detailing exteroceptive and interoceptive processing in autism and discuss their neurobiological basis as well as potential links and analogies between sensory domains. Results: Many atypicalities of autistic perception described in the literature can be explained either by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 214 publications
(398 reference statements)
1
19
0
Order By: Relevance
“…In our study, we also observed a larger dSSP score variability in autistic individuals than in controls, which is in line with the heterogeneity reported in autism spectrum in many research areas, such as brain imaging (Masi et al, 2017). Our results stressed further the need for partial phenotypes beyond categorical diagnosis to help in patients' stratification and delineate more homogeneous subgroups (Proff et al, 2021;Wolfers et al, 2019). The dSSP score may offer a relevant setting to explore the heterogeneity in autism spectrum (Lombardo et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we also observed a larger dSSP score variability in autistic individuals than in controls, which is in line with the heterogeneity reported in autism spectrum in many research areas, such as brain imaging (Masi et al, 2017). Our results stressed further the need for partial phenotypes beyond categorical diagnosis to help in patients' stratification and delineate more homogeneous subgroups (Proff et al, 2021;Wolfers et al, 2019). The dSSP score may offer a relevant setting to explore the heterogeneity in autism spectrum (Lombardo et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…However, this research was primarily assessed using a self-report measure of interoception (TAS) in combination with cardiac interoception tests. Sensory alterations are well established in autism and more nuanced interoceptive tests are needed across a variety of axes to better understand the nature of altered interoceptive sensory processing in autism, where changes in temperature perception, slow affective touch, and gastric processing are documented (see [125] for a review).…”
Section: Measuring Dimensions Of Interoception In Mental Healthmentioning
confidence: 99%
“…Autistic people have also been shown to excel at producing novel responses on creative tasks 126 and are increasingly recognized for their creative talents 127 , with major companies investing in autistic people’s ‘out-of-the-box’ thinking 128 . These strengths have been linked to autistic people’s different way of perceiving the world, including detail-focused processing style 129 and enhanced perceptual abilities 130 , which might be underpinned by heightened sensory perception 131 .…”
Section: A Capabilities Approach To Autistic Livesmentioning
confidence: 99%